Experimental Investigation of CaMnO3−δ Based Oxygen Carriers Used in Continuous Chemical-Looping Combustion - Peter Hallberg; Malin Källén; Dazheng Jing; Frans Snijkers; Jasper van Noyen; Magnus Rydén; Anders Lyngfelt (International Journal of Chemical Engineering)
Three materials of perovskite structure, CaMn1−xMxO3−δ (M = Mg or Mg and Ti), have been examined as oxygen carriers in continuous operation of chemical-looping combustion (CLC) in a circulating fluidized bed system with the designed fuel power 300 W. Natural gas was used as fuel. All three materials were capable of completely converting the fuel to carbon dioxide and water at 900°C. All materials also showed the ability to release gas phase oxygen when fluidized by inert gas at elevated temperature (700–950°C); that is, they were suitable for chemical looping with oxygen uncoupling (CLOU). Both fuel conversion and oxygen release improved with temperature. All three materials also showed good mechanical integrity, as the fraction of fines collected during experiments was small. These results indicate that the materials are promising oxygen carriers for chemical-looping combustion.